2014
DOI: 10.1186/2197-425x-2-12
|View full text |Cite
|
Sign up to set email alerts
|

A standardized model of brain death, donor treatment, and lung transplantation for studies on organ preservation and reconditioning

Abstract: BackgroundWe set a model of brain death, donor management, and lung transplantation for studies on lung preservation and reconditioning before transplantation.MethodsTen pigs (39.7 ± 5.9 Kg) were investigated. Five animals underwent brain death and were treated as organ donors; the lungs were then procured and cold stored (Ischemia). Five recipients underwent left lung transplantation and post-reperfusion follow-up (Graft). Cardiorespiratory and metabolic parameters were collected. Lung gene expression of cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Transcription of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) is induced by TNF-α and IL-1β [ 50 ]. The expressions of ICAM-1 and VCAM-1 have been reported to be increased in toxic and BD-induced models of acute lung injury [ 48 , 49 ] but remained unchanged in the present study as reported by other authors [ 48 ]. The activation of apoptosis suggested by the increased lung apoptotic rate measured by TUNEL immunochemistry in the present study is also consistent with previous reports [ 51 ] and seems to be closely related to the activation of inflammatory processes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Transcription of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) is induced by TNF-α and IL-1β [ 50 ]. The expressions of ICAM-1 and VCAM-1 have been reported to be increased in toxic and BD-induced models of acute lung injury [ 48 , 49 ] but remained unchanged in the present study as reported by other authors [ 48 ]. The activation of apoptosis suggested by the increased lung apoptotic rate measured by TUNEL immunochemistry in the present study is also consistent with previous reports [ 51 ] and seems to be closely related to the activation of inflammatory processes.…”
Section: Discussionsupporting
confidence: 83%
“…Although IL-1β and TNF-α are physiologic stimuli for the synthesis of IL-6, we failed to find altered expression for them after brain death. Several studies have shown elevated lung TNF-α and IL-1β expression [ 42 , 47 , 48 ] or no significant change in lung tissue TNF-α and IL-1β expression [ 49 ], suggesting variable expression of these cytokines after brain death. Lung tissue expression in IL-6 and pro-inflammatory IL-6/IL-10 returned to normal level five hours after brain death, suggesting their implication as an early inflammatory response to hemodynamic stress.…”
Section: Discussionmentioning
confidence: 99%
“…These anatomical differences constitute a limit to a direct extrapolation of murine models of chronic lung disease, including ours, to the human situation. Eventually, alternative animal models, e.g., pigs or ferrets, will unravel the role of basal progenitor cells, as these species also contain club cells and bronchial progenitor cell populations in the distal airways (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…WLST is also allowed by Italian law but has not become common practice yet and has been only recently codified. After a long pre-clinical phase ( 5 , 6 , 7 ), we refined an original two-steps protocol to manage lungs from DCD donors to overcome the long acirculatory period ( 8 ). First, by leveraging the possibility of dissociating ischemia from hypoxia, we adopted an open lung strategy for in-situ lung preservation even for prolonged periods, without topical cooling.…”
Section: Introductionmentioning
confidence: 99%